Wealth effects and the consumption of Italian households in the Great Recession - Renata Bottazzi; Serena Trucchi; Matthew Wakefield (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2017)
We estimate marginal propensities to consume from wealth shocks for Italian households in the early part of the Great Recession. Large asset price shocks in 2008 underpin an IV estimator. A euro fall in risky financial wealth resulted in cuts in annual total (non-durable) consumption of 8.5] 9 (5.5-5.7) cents. There is evidence of effects on food spending. Responses of total and nondurable spending to changes in housing wealth are 0.2 to 0.3 cents/euro. Point estimates of the effect of the financial wealth shock are larger if the youngest and/or oldest households are excluded. Results indicate that responses to the wealth shock were stronger for those who became pessimistic about the stock market, and for those owners of risky assets who also held mortgage debt. Counterfactuals indicate financial wealth effects were important (relative to other factors) for consumption falls in Italy in 2007/08.
Keywords: D12; D91; 330; Wealth effects; household consumption; the Great Recession